A hybrid digital parenting programme delivered within the Malaysian preschool system: protocol for a feasibility study of a small scale cluster randomised factorial trial - Cooper, H; Nadzri, FZM; Vyas, S; Juhari, R; Ismail, N; Arshat, Z; Rajandiran, D; Calderon, F; Markle, L; Vallance, I; Melendez-Torrez, GJ; Facciolà, C; et al. (JMIR Publications, 2024)
Background: Achieving Sustainable Development Goal 4, and in particular target 4.2, to ensure that all children have access to quality early childhood development, care and preprimary education so that they are ready for primary education, is far from being attained. COVID-19 further compromised progress by disrupting early education, reducing access to wellbeing resources, and increasing family violence. Evidence from low- and middle-income countries suggests in-person parenting interventions are effective at improving child learning and preventing violence. Scaling-up these programmes, however, is challenged because of resource constraints. Integrating digital and human-delivered intervention components is one potential solution to addressing these challenges. There is a need to understand the feasibility and the effectiveness of such interventions in low resource settings including Malaysia.